Redescription of the pupae of Hyperalonia morio morio (Fabricius), 1775 (Diptera, Bombyliidae, Anthracinae, Exoprosopini) - Cunha, André Mallemont; Lamas, Carlos José Einicker (Zootaxa, 2004)
The pupa of Hyperalonia morio morio (Fabricius), 1775 is redescribed and illustrated. Rubrica nasuta (Christ, 1791) is confirmed as the only known host for H. m. morio.